Precarização do trabalho e da vida: quando o retrocesso de direitos atinge a saúde mental dos trabalhadores - Andretta, Bruno dos Santos (2019)
Labor has been suffering constant change throughout history, be it by advancing knowledge and technology, or by increasing competition in the world market as a whole. The level of demand, when it comes to productivity (directly proportional to labor intensity), is increasing, triggering a series of negative consequences for the worker. Therefore, going beyond physical harm, it is known that there are several psychosocial risks (many times invisible) that affect the working class. This scenario is excessively aggravated in the social context hit by the unmeasured neoliberal offensive. Thus, it is pressing to consider what relations and consequences can be pointed out between the precariousness of work, the impact on the mental health of workers, and the recent flexibilization of the judiciary system - being this the objective of the research. To this end, we sought to draw an overview of the precariousness of labor relations, with the understanding of the historical phenomena related to the organization of work, going through questions related to the role of the capital (through Toyotism) as an element that is closely connected to the psychism and consequent impacts on the mental health of the worker, as to, in a third moment, bring considerations about the current moment of legislative flexibilization of the diplomas related to work (especially Law No. 13,467/2017). The research was conducted through bibliographic and documental survey. The approach method used is the deductive one, establishing an interdisciplinary (and also dialectical) view between Law and other areas of knowledge. The procedure methods adopted are the historical and monographic ones, aiming at understanding the historical, social, and economic contexts, to then promote the necessary analysis and reflections on the legal context related to the theme. Finally, it is concluded that, yes, the recent changes in labor legislation, incorporated to the attacks of the socioeconomic context permeated by neoliberalism, have a direct and important impact on the already affected quality of life and mental well-being of the worker, demanding, above all, to establish the necessary effectiveness of decent work conceptions, human dignity, and sustainability.